RELATIONSHIP OF LIPID PROFILE AND IMMUNE STATUS IN THE DYNAMICS OF LONG-TERM EXPOSURE TO COAL-ROCK DUST ON THE BODY (EXPERIMENTAL STUDIES) - Казицкая, Анастасия Сергеевна; Жукова, Анна Геннадьевна; Бугаева, Мария Сергеевна; Жданова, Наталья Николаевна (Medicine in Kuzbass, 2017)
Subject. The relationship between lipid metabolism and immune reactivity in the dynamics of long-term exposure to coal-rock dust (CRD) on the body.Objective. In the experiment to examine the impact of the changes in the lipid profile on immune status under the conditions of long-term exposure to CRD on the body.Methods. The experiments were carried out on 110 white male rats weighing 200-250 g. The inhalation method was used for modeling that best fits the conditions of coal-mine production. Animals were divided into 2 groups: the control (n = 30); the experiment (n = 80), that are the rats who inhaled CRD with a particle size of up to 5 microns in an average concentration of 50 mg/m3 for 4 hours daily for 12 weeks.Main results. Early terms of the CRD impact are characterized by the activation of the immune system against the background of metabolic shifts as well as by morphological changes of the immune nature in the bronchopulmonary system and liver of the rats that can be regarded as compensatory-adaptive. Prolonged exposure to the dust factor leads to an increase in dyslipidemia, which contributes to the development of immune imbalance as well as morphological changes that are indicative of the chronic inflammation and disturbance of compensatory mechanisms.Field of application. The results of the conducted experimental studies broaden the fundamental ideas about the mechanisms of immune body defense. The detection of pathogenetic mechanisms underlying the formation and course of occupational diseases allows assessing the functional state of the organism at the stage of pre-existing disease, revealing the initial signs of developing pathology and determining the ways of their correction.Conclusions. CRD intake is characterized by the development of metabolic changes, which are closely related to immune reactivity. An integrated approach to the study of occupational and industrially-caused pathology makes it possible to assess the functional state of the organism at the early stages of the disease development and to substantiate diagnostic markers for determining the state of pre-existing disease and for conducting timely preventive measures.
Keywords: occupational diseases; coal-rock dust; experimental studies; immunological reactivity; lipid profile